“History as Revelation” in the Theology of the Social Gospel - King, William McGuire (Harvard theological review, 1983)
Historical studies of the American social gospel have concentrated on the social and economic viewpoint of the movement. Such a focus is understandable since the fundamental premise of the social gospel was the belief that social change should be controlled and directed through the rational application of religious ideals. Scholarly interest in the movement has thus naturally gravitated towards questions of practical import: how the social gospel galvanized the churches to social action; how it challenged dominant political assumptions; how it contributed to the success of the progressive movement; how it helped to promote cooperative social ideals and a limited type of Christian socialism; and how it struggled with the problem of finding a realistic political philosophy.